Current relevance in the Croatian perfekt tense: speaker's cognitive space - Stanojević, Mateusz-Milan; Geld, Renata (2005)
Traditional grammars of Croatian (Katičić 1991:50 ff) claim that the Croatian perfekt tense refers to an action that was completed in the past, but that has consequences for the present (Katičić 1992:176). In the analysis of the English present perfect tense, this notion is dubbed "current relevance" (see, e.g., Comrie 1985:25 ; Palmer 1987:48-51 ; Langacker 1991:211-215). Croatian grammars also recognize that in certain contexts the perfekt no longer connects the consequences of the action with the present moment. A typical example of such "neutralization" (cf. Katičić 1992:179) is: Konj je preskočio grabu ('The horse has jumped over/jumped over the ditch ; lit. 'Horse-NOM be-imperf-pres-3rd sg jump over-perf-participle-sg-masc ditch-ACC'). Katičić claims that in this sentence "it is not necessarily important to say that the horse is on the other side of the ditch, so we are left with the fact that it jumped over the ditch at a particular time in the past". In a previous paper we have proved that current relevance has no symbolic correspondents in the grammar of Croatian and that its inclusion into the analysis of the Croatian perfekt tense is a result of merging its contextual with its symbolic value. In this paper we wish to expand on this claim, and show that the symbolic value of the perfekt tense in both the so-called "neutralized" and the "non-neutralized" contexts is to denote past, and that the current relevance meaning is inferred from the aspect of the verb and the participle. The Croatian perfekt is formed using the imperfective present tense of the verb biti ('to be') and the l-participle of the content verb, which is inflected for gender and number. In this paper, we will discuss the status of current relevance in the native speakers' knowledge of the perfekt. We wish to argue that the current relevance is the result of inference that is a product of the interplay between the meaning of l-participle and the aspectual characteristics of the content verb. It is our intention to demonstrate that the symbolic value of the perfekt is primarily to denote past. More specifically, we wish to claim that the Croatian l-participle, by focusing on the end part of the event, has a role of cancelling the process designated by the content verb. Its role is the same with both perfective and imperfective processes and it is the perfective aspect that is (co-)responsible for the construal implying current relevance. Moreover, we wish to consider the claim by some authors (cf. Belaj 2004: 66 ; Dubravčić 1985:267) that the usage of the perfekt in the passive voice in most cases implies current relevance. In the light of this claim, we further hypothesize that, contrary to the role of l-participle, the role of the n-participle is non-cancelling. Therefore, in the passive form of the perfekt tense, the n-participle always contributes the current relevance meaning. We will attempt to support our claims based on a cognitive linguistic analysis of examples from Croatian grammars as well as on speakers' judgments concerning the means of expressing current relevance in Croatian. We hypothesize that with both perfective and imperfective processes, the native speakers of Croatian will recognize the usage of perfekt to denote past and assign current relevance meaning to other contextual clues. If our claims are substantiated, this calls for a significant revision of the description of the Croatian perfekt tense, as well as other tenses placed in the traditional two-fold system of completed and non-completed past, present and future.
Projekt MZOS
Projekt MZOS
ENG